Characterization of vancomycin-resistance vanD gene clusters in the human intestinal microbiota by metagenomics and culture-enriched metagenomics. Issue 2 (24th March 2023) - Brochu, Eliel; Huletsky, Ann; Boudreau, Dominique K; Raymond, Frédéric; Bérubé, Ève; Ouameur, Amin Ahmed; Frenette, Johanne; Boissinot, Maurice; Corbeil, Jacques; Bergeron, Michel G
Abstract: Objectives: To characterize vancomycin-resistance vanD gene clusters and potential vanD -carrying bacteria in the intestinal microbiota of healthy volunteers exposed or not to β-lactam antibiotics. Methods: Stool samples were collected before and after 7 days of cefprozil β-lactam antibiotic exposure of 18 participants and six control participants who were not exposed to the antibiotic at the same time points. Metagenomic sequencing and culture-enriched metagenomic sequencing (with and without β-lactam selection) were used to characterize vanD gene clusters and determine potential vanD -carrying bacteria. Alteration by antimicrobials was also examined. Results: Culture enrichment allowed detection of vanD genes in a large number of participants (11/24; 46%) compared to direct metagenomics (2/24; 8%). vanD genes were detected in stool cultures only following β-lactam exposure, either after β-lactam treatment of participants or after culture of stools with β-lactam selection. Six types of vanD gene clusters were identified. Two types of vanD cluster highly similar to those of enterococci were found in two participants. Other vanD genes or vanD clusters were nearly identical to those identified in commensal anaerobic bacteria of the families Lachnospiraceae and Oscillospiraceae and/or bordered by genomic sequences similar or related to these anaerobes, suggesting that they are the origin or carriers of vanD . Conclusions: This study showed that culture-enriched metagenomics allowed detection of vanD genes not detected by direct metagenomics and revealed collateral enrichment of bacteria containing vancomycin-resistance vanD genes following exposure to β-lactams, with a higher prevalence of the most likely gut commensal anaerobes carrying vanD . These commensal anaerobes could be the reservoir of vanD genes carried by enterococci.